The external financing of economic development : international flow of long-term capital and official donations, 1962-1966 - United Nations Department of Economic and Social Affairs (New York : United Nations, 1968)
As in the case of previous reports in the series, this report contains the most recent information regarding the movement of capital, but in addition provides a statistical analysis of the nature and magnitude of the resources transferred in the previous ten years. It also contains information regarding the movement of capital and investment income from developing countries.
Report of the Secretary-General.
Includes bibliographical footnotes.
ne 16/04/2019
Ref
Keywords: Economic development